Jenny Lind. Of Echoes and Traces - Anne Harley; Andrea Zittlau (Cahiers Victoriens et Edouardiens)
In September 1850, the celebrated soprano Jenny Lind, better known as the Swedish Nightingale, arrived in the United States for what would be her last major musical tour. Her wild success in the young nation was built upon an advertising campaign by Phineas Taylor Barnum that leveraged her talent and various aspects of her identity. In this article, we consider the music written for Lind and how the sound she produced impacted her audiences, as well as those who did not even hear her. It is not an attempt to recreate Lind’s voice but to mark its absence by ‘audiolizing’ the genres it produced. We describe the tension between the written sheet music found in the archives and the corresponding performances by Lind and her imitators, as described in the press. Lind’s voice communicated to American society in several registers simultaneously: her vocal performance is variously described as a model for the voice of the masses, a respondent in sing-along sessions with audiences in the street, and also as an indescribable vehicle for spiritual transcendence. We will trace the correspondence of these identities and in so doing, hope to amplify the popular soundscapes of the mid-nineteenth century America.